2020
DOI: 10.1017/s0029665120000439
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial DNA methylation is associated with Mediterranean diet adherence in a population of older adults with overweight and obesity.

Abstract: AbstractIntroductionAdherence to the Mediterranean dietary pattern (MeDiet) and adiposity, respectively, decreases and increases the risk of multiple common age-related diseases through several mechanisms including inflammation, reactive oxygen species (ROS) production in the mitochondria, and DNA methylation. For example, adverse changes in platelets from obese and overweight adults include hyper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 0 publications
0
8
1
Order By: Relevance
“…For these reasons, nutrition, the redox system, and epigenetics are strictly interconnected. Previous studies suggested a potential impact of diet on mtDNAcn [ 20 , 21 ] and also on mtDNA methylation [ 22 , 23 ]. Indeed, it has recently been demonstrated that DNA methylation occurs not only in the nDNA but also in the mtDNA (especially in the displacement loop or D-loop) [ 24 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For these reasons, nutrition, the redox system, and epigenetics are strictly interconnected. Previous studies suggested a potential impact of diet on mtDNAcn [ 20 , 21 ] and also on mtDNA methylation [ 22 , 23 ]. Indeed, it has recently been demonstrated that DNA methylation occurs not only in the nDNA but also in the mtDNA (especially in the displacement loop or D-loop) [ 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, the mechanistic effects that it exerts on mtDNA replication and transcription are still discussed [ 25 , 26 ]. Alterations of mtDNA methylation have been associated with multifactorial diseases such as cardiovascular diseases (CVDs) [ 27 , 28 ] and obesity [ 29 ], as well as with environmental exposures including pollutants [ 30 , 31 ] and nutrition [ 22 ]. For this reason, mtDNA methylation appears as a promising mediator between environmental exposure (i.e., diet) or metabolic conditions (i.e., obesity) and mitochondrial health.…”
Section: Introductionmentioning
confidence: 99%
“…However, a certain responsiveness of the mitochondrial epigenome to external stimuli, including but not limited to dietary elements, has been postulated [65,67,120]. Remarkably, Corsi and colleagues recently demonstrated that mtDNA methylation can change accordingly to the adherence to the Mediterranean diet [250], corroborating the hypothesis of a potential role of nutrition in the modulation of mtDNA methylation.…”
Section: Antioxidants and Mitochondria: From The General Function To mentioning
confidence: 91%
“…[18] Methylation has been measured throughout the mitochondrial genome, in CpG sites but also in CpH (non-CG) dinucleotides, [19,20] and differ among tissues and cell types. [21,22] Strand-specific methylation levels in the D-loop area of mtDNA have been found as well and reported to vary in response to environmental stimuli, [23][24][25] including diet, [26][27][28] even though a clear mechanistic role of this epigenetic modification has not been defined yet.…”
Section: Introductionmentioning
confidence: 99%
“…Only a few studies reporting on the impact of diet on mtDNAcn and methylation have been published to this date. [26][27][28] Therefore, this research aims to test whether diet, TMA, and TMAO are associated with levels of mitochondrial DNA copy number and methylation in a group of healthy subjects having extremely healthy or unhealthy dietary patterns.…”
Section: Introductionmentioning
confidence: 99%